Comparative Analysis of Isotonic Drinks and Water Consumption After Exercise: A Study on Teenagers' Metabolic Response and Health Implications - Silaen, Ayleen Latiesha; Avinash, Lachmanan; Yang, Louisa Marvelin; Nosapratama, Heslian Swiphatiklientine (Jurnal Pendidikan Makarios, 2024)
This study aims to show a comparison of the effects of consuming isotonic drinks and water after exercising. Many believe that isotonic drinks will help restore stamina and strength when exercising. It is for this reason that athletes consume it, and many recommend it. However, this study will find out and prove whether this hypothesis is true for all groups, especially teenagers. To prove it, several students from Makarios Christian School, samples of students of grade 10 to 12 were taken, while doing exercise with the same intensity. The data were taken by using the theory of Blood Glucose Testing by Brown, et. al. (2019) and Sandercock and Brodie, (2006) as the secondary theory of heart rate variability to assess the effect of isotonic drink and pH on metabolism and autonomic control during exercise. The categories that drank water and isotonic drinks were separated and the data was collected. As a result: 1) This study showed the effects of drinks consumed on the body's metabolism, especially pulse rate, blood sugar and blood pressure. 2) It was found that consuming isotonic drinks will provide electrolytes so that those excreted through sweat can be returned back, so that the body does not lack electrolytes or ions.On the other hand, even though water does not contain electrolytes, this also means there are no carbohydrates or sugar. 3) The pH level of water was also neutral, so the body was helped to return its level back to neutral, whereas isotonic drinks had a pH with an acidic level. This study serves as a valuable resource for athletes, health enthusiasts, and educators, providing evidence-based insights into the nuanced effects of isotonic drinks and water on the body post-exercise, particularly among the adolescent demographic.